Measurement of skin thickness and skin elasticity to evaluate the effectiveness of intensive decongestive treatment in patients with lymphoedema: a prospective study. Issue 3 (27th November 2013) - Hacard, F.; Machet, L.; Caille, A.; Tauveron, V.; Georgescou, G.; Rapeneau, I.; Samimi, M.; Patat, F.; Vaillant, L.
<x xml:space="preserve">Abstract</x> Background Complex decongestive physiotherapy (CDP) is used to treat patients with severe lymphoedema. The efficacy of CDP is usually quantified by calculating limb volume from repeated measurements of circumference at least 10 points before and after treatment of an affected limb. Measurement is time‐consuming and operator‐dependent. Objectives To determine whether decreased dermal thickness is correlated with decreased volume after intensive CDP. Methods A consecutive series of patients admitted for intensive CDP were studied over a 6‐month period. Before and after CDP, we measured circumference, dermal thickness elasticity and finally improvement in quality of life using a visual analogue scale (VAS). Results Thirty patients were included in the study. Only three patients were previously untreated. The average relative reduction in limb volume was 4% and the reduction in the dermal thickness was 15% (correlation: r = 0.37, P = 0.05). Viscoelasticity was decreased by 13%. VAS quality of life score was improved by 30%. Conclusion Changes in dermal thickness are slightly correlated with volume changes before and after 5‐day intensive CDP in a selected series of patients previously treated at home.